Descripción de un caso de adenomatosis erosiva del pezón: tratamiento quirúrgico - Chavez-Diaz, M (2023)
Erosive adenomatosis is a rare benign neoplasm that affects the nipple. Characterized by erosion, telorrhoea, telorrhagia, nodularity, pruritus and erythema, causing a progressive destructive process of the nipple, which can be confused with Paget's disease; which is why knowledge of this pathology is essential to avoid surgical overtreatment. We present the case of a 35-year-old patient diagnosed and treated with surgery, as well as a review of the literature on this entity. © 2023